2009
DOI: 10.1002/ana.21801
|View full text |Cite
|
Sign up to set email alerts
|

High‐intensity focused ultrasound for noninvasive functional neurosurgery

Abstract: (2009

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
331
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 407 publications
(336 citation statements)
references
References 22 publications
2
331
0
3
Order By: Relevance
“…These findings were consistent with those previously reported in a trial of MR imagingguided focused sonography lesioning of the contralateral thalamus for neuropathic pain. 10 Zone III was consistent with vasogenic edema 26,27 ; it was typically seen at 24 hours and 1 week and then resolved. This appearance of lesions and their evolution with time was similar to the imaging findings observed for stereotactic radiofrequency thalamotomies but quite different from those observed with gamma knife radiosurgery.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…These findings were consistent with those previously reported in a trial of MR imagingguided focused sonography lesioning of the contralateral thalamus for neuropathic pain. 10 Zone III was consistent with vasogenic edema 26,27 ; it was typically seen at 24 hours and 1 week and then resolved. This appearance of lesions and their evolution with time was similar to the imaging findings observed for stereotactic radiofrequency thalamotomies but quite different from those observed with gamma knife radiosurgery.…”
Section: Discussionmentioning
confidence: 92%
“…Further investigation in animal models is needed to elucidate the exact nature of this enhancement, which might be related to neovascularization. 32 Of note, in the previous application of MR imaging-guided focused sonography for neuropathic pain syndromes, 10 enhancement was seen at 24 hours and had resolved by 48 hours. Patients were not imaged beyond 48 hours.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It does not involve ionizing radiation, is not limited by trajectory restrictions, and is not preclusive for later MRI diagnostics and treatment options. Several clinical phase I trials have demonstrated the feasibility and safety of using tcMRgFUS to treat a variety of functional brain disorders, such as chronic neuropathic pain [2], essential tremor [3,4], or tremordominant Parkinson's disease [5] through thermal ablation of thalamic and subthalamic targets with submilimeter precision [6]. Accordingly, the InSightec Neuro system used in these trials received CE marking for functional neurosurgery by the end of 2012.…”
Section: Introductionmentioning
confidence: 99%